Do Spatial Boundaries Matter for Exploring the Impact of Community Green Spaces on Health? - Shin, Jong Cheol (Int J Environ Res Public Health, 2020)
Green space exposure is thought to have a positive influence on physical activity behavior and overall health. However, the literature remains equivocal, and green space measurement methods remain complicated. Using data from the Illinois Behavioral Risk Factor Surveillance System, this study examines the influence of green space on health-related factors, such as exercise, physical health, and mental health. Moreover, we explore the methods for measuring community green space via various spatial boundaries and green space resources. The results show that combining two contextually designated census boundaries and a measure of green space with seasonality were the best spatial conceptualizations for capturing community green space. Moreover, the findings showed a positive influence of green space exposure on health outcomes. These findings highlight the importance of considering geographic contexts of daily human behaviors and green space seasonality in providing a better understanding of the influence of community activity space on environmental exposure measurement. Further, this work contributes to community planning for encouraging health-promoting behaviors.